A glucose-blue light AND gate-controlled chemi-optogenetic cell-implanted therapy for treating type-1 diabetes in mice - Li, Chi-Yu; Wu, Ting; Zhao, Xing-Jun; Yu, Cheng-Ping; Wang, Zi-Xue; Zhou, Xiao-Fang; Li, Shan-Ni; Li, Jia-Da (Frontiers in Bioengineering and Biotechnology, 2023)
Exogenous insulin therapy is the mainstay treatment for Type-1 diabetes (T1D) caused by insulin deficiency. A fine-tuned insulin supply system is important to maintain the glucose homeostasis. In this study, we present a designed cell system that produces insulin under an AND gate control, which is triggered only in the presence of both high glucose and blue light illumination. The glucose-sensitive GIP promoter induces the expression of GI-Gal4 protein, which forms a complex with LOV-VP16 in the presence of blue light. The GI-Gal4:LOV-VP16 complex then promotes the expression of UAS-promoter-driven insulin. We transfected these components into HEK293T cells, and demonstrated the insulin was secreted under the AND gate control. Furthermore, we showed the capacity of the engineered cells to improve the blood glucose homeostasis through implantation subcutaneously into T1D mice.